Patterns of alteration in boar semen quality from 9 to 37 months old and improvement by protocatechuic acid - Ruizhi Hu; Xizi Yang; Jiatai Gong; Jing Lv; Xupeng Yuan; Mingkun Shi; Chenxing Fu; Bie Tan; Zhiyong Fan; Liang Chen; Hongfu Zhang; Jianhua He; et al. (Journal of Animal Science and Biotechnology, 2024)
Abstract Background Comprehending the patterns of alteration in boar semen quality and identifying effective nutritional interventions are crucial for enhancing the productivity of commercial pig systems. This study aimed to examine the alteration in semen quality in boars, and assess the impact of protocatechuic acid (PCA) on semen quality during the phase of declining semen quality. Methods In Exp. 1, a total of 38 Pig Improvement Company (PIC) boars were selected and their semen quality data were recorded from the age of 9 to 37 months. In Exp. 2, 18 PIC boars (28 months old) were randomly assigned into three groups (n = 6) and fed a basal diet, a basal diet containing 500 or 1,000 mg/kg PCA, respectively. The experiment lasted for 12 weeks. Results The semen volume, concentration, and total number of spermatozoa in boars exhibited an increase from 9 to 19 months old and showed a significant linear decreased trend in 28, 24, and 22 months old. Sperm motility displayed an upward trajectory, reaching its peak at 20 months of age, and showed a significant linear decreased trend at 20 months old. Dietary supplementation of PCA demonstrated an effect to mitigate the decrease in semen volume, concentration of spermatozoa, total number of spermatozoa (P > 0.05), and significantly increased the sperm motility (P < 0.05). Moreover, supplementation of 1,000 mg/kg PCA significantly increased the sperm viability (P < 0.05). Analysis on cellular signaling pathways revealed that PCA restored serum testosterone levels and alleviated oxidative damage by upregulating the expression of HO-1, SOD2, and NQO1 in testicular stromal cells. Notably, PCA can enhance phosphorylation by selectively binding to AMP-activated protein kinase (AMPK) protein, thereby improving sperm mitochondrial function and augmenting sperm motility via PGC-1/Nrf1. Conclusions These data elucidated the pattern of semen quality variation in boars within the age range of 9 to 37 months old, and PCA has the potential to be a natural antioxidant to enhance sperm quality through modulation of the AMPK/PGC-1/Nrf1 signaling pathway.